International lessons: youth unemployment in the global context - Crowley, Lizzie; Jones, Katy; Cominetti, Nye; Gulliford, Jenny (London, 2013)
"The UK has a major youth unemployment problem. Almost a million young people in the UK are unemployed – and the size of this group was rising even during times of economic growth.